Deep Learning-Based Universal Expert-Level Recognizing Pathological Images of Hepatocellular Carcinoma and Beyond - Chen, Wei-Ming; Fu, Min; Zhang, Cheng-Ju; Xing, Qing-Qing; Zhou, Fei; Lin, Meng-Jie; Dong, Xuan; Huang, Jiaofeng; Lin, Su; Hong, Mei-Zhu; Zheng, Qi-Zhong; Pan, Jin-Shui (Frontiers in Medicine, 2022)
Abstract Background & Aims: We aim to develop a diagnostic tool for pathological-image classification using transfer learning that can be applied to diverse tumor types. Methods: Microscopic images of liver tissue with and without hepatocellular carcinoma were used to train and validate the classification framework based on a convolutional neural network. To evaluate the universal classification performance of the artificial intelligence (AI) framework, histological images from colorectal tissue and the breast were collected. Images for the training and validation sets were obtained from the Xiamen Hospital of Traditional Chinese Medicine, and those for the test set were collected from Zhongshan Hospital Xiamen University. The accuracy, sensitivity, and specificity values for the proposed framework were reported and compared with those of human image interpretation. Results: In the human–machine comparisons, the accuracy of the AI framework was 98.5%, whereas that of human experts fluctuated between 93.0% and 95.0%. Based on transfer learning, the accuracies of the AI framework in classifying colorectal carcinoma and breast invasive ductal carcinoma were 96.8% and 96.0%, respectively. Conclusion: The performance of the proposed AI framework in classifying histological images with hepatocellular carcinoma was comparable to the classification performance achieved by human experts, indicating that extending the proposed AI’s application to diagnoses and treatment recommendations is a promising area for future investigation.